Defining the student burnout construct: a structural analysis from three burnout inventories - Maroco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Ammons Scientific, Ltd, 2012)
College student burnout has been assessed mainly with the Maslach Burnout Inventory (MBI). However, the construct's definition and measurement with MBI has drawn several criticisms and new inventories have been suggested for the evaluation of the syndrome. A redefinition of the construct of student burnout is proposed by means of a structural equation model, reflecting burnout as a second order factor defined by factors from the MBI-Student Survey (MBI-SS); the Copenhagen Burnout Inventory-Student Survey (CBI-SS) and the Oldenburg Burnout Inventory-Student Survey (OLBI-SS). Standardized regression weights from Burnout to Exhaustion and Cynicism from the MBI-SS scale, Personal Burnout and Studies Related Burnout from the CBI, and Exhaustion and Disengagement from OLBI, show that these factors are strong manifestations of students' burnout. For college students, the burnout construct is best defined by two dimensions described as "physical and psychological exhaustion" and "cynicism and disengagement."